Implementasi Kebebasan Berakad Pada Akad-Akad Perbankan Syariah Di Kota Pekanbaru Dalam Hukum Islam: Implementasi Kebebasan Berakad Pada Akad-Akad Perbankan Syariah Di Kota Pekanbaru Dalam Hukum Islam - Azani, Muhammad (Program Studi Magister Ilmu Hukum Sekolah Pasca Sarjana Universitas Lancang Kuning, 2024)
freedom of contract in terms of making/entering conditions in it is only a quasi-freedom of contract. This means that freedom of contract in Islamic law has not been fully implemented in existing contracts in sharia banking in Indonesia. Because on the one hand, in various contracts there are clauses/conditions that contain elements of freedom of contract based on Islamic law, but on the other hand they still contain elements of freedom of contract based on the conventional system. This is because the restrictions on freedom of contract in Islamic law are not fully respected by BUS. Implementation of freedom of contract in making clauses/entering conditions in the contract in BUS customers cannot yet exercise full freedom of rights because they receive a standard contract from a sharia bank. If viewed based on the theory of maslahah al-murlah, the clauses/conditions in the standard contract do not fully meet the criteria of benefit and are not in accordance with the concept of freedom of contract in Islamic law